Diversity of Fusarium Endophytes Isolated from Wild Bananas in Pandenglang, Indonesia - Nani Maryani; Siti Yulianti; Indriati Ramadhani; Rida Oktorida Khastini; Suroso Mukti Leksono (Universitas Gadjah Mada, 2023)
A group of Fusarium spp., in the Fusarium oxysporum species complex is known as pathogens on bananas, i.e., Fusarium wilt or Panama Disease. However, many Fusarium spp. are also known to be endophytes inside healthy banana plants and have been less explored and investigated. Fusarium endophytes have been demonstrated to be effective against the Fusarium pathogen that causes wilting in some crops such as tomatoes and watermelon. Thus, we explored endophytes Fusarium from local bananas in Pandenglang Banten for further use as biocontrol of Fusarium wilt. Four wild banana accessions were identified, from which 9 Fusarium isolates recovered from its pseudostems asymptomatic plants. All isolates were characterized based on their morphological characters and sequence of the Internal Transcribed Spacer (ITS) gene. These isolates belong to four complexes of Fusarium i.e. Fusarium equiseti species complex, Fusarium oxysporum species complex, Fusarium sambucinum species complex, and Fusarium solani species complex (currently described as Neocosmospora). Further study on molecular characterization of these isolates using specific genes and their potential antagonists of pathogens still needs to be discovered for other use as a biocontrol against Fusarium wilt.